EVALUASI FAKTOR YANG BERHUBUNGAN DENGAN HIPERTENSI PADA LANSIA - Darmawan, Agus Citra; Fahdi, Faisal Kholid; Hidayati, Rahma (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Knowing what factors influence the incidence of hypertension in the elderly is a very important effort. This observational analytical research with a cross-sectional approach aims to determine the relationship between age, gender, family history, smoking habits, exercise habits, coffee drinking habits, excessive salt consumption, type A personality, obesity, stress levels and identify the most important factors. dominantly influences the incidence of hypertension in the elderly. The research subjects were 91 respondents. Hypertension was categorized using JCN, obesity using BMI, stress using the Holmes scale and personality type using the Rosenman Scale. Interview guidelines were used to collect data on age, gender, family history, smoking habits, exercise habits, coffee drinking habits, excessive salt consumption, personality type, obesity, and stress levels. Factors that influence hypertension in the elderly include; age, family history, obesity and stress. Age in this study is the factor that has (OR=53.94) the most influence on the incidence of hypertension in the elderly.